Post-DDAVP Thrombocytopenia in Type 2B von Willebrand Disease Is not Associated with Platelet Consumption: Failure to Demonstrate Glycocalicin Increase or Platelet Activation - Casonato, A.; Steffan, A.; Pontara, E.; Zucchetto, A.; Rossi, C.; De Marco, L.; Girolami, A. (Thrombosis and Haemostasis, 1999)
Thrombocytopenia is frequently reported in type 2B von Willebrand disease (vWD), and thought to be related to the abnormally high affinity of 2B von Willebrand factor (vWF) for platelet GPIb-IX. To gain an insight into the nature of this thrombocytopenia, we measured plasma glycocalicin (GC) levels (as a marker of platelet turnover), and platelet surface expression of the alpha granule protein P-selectin (as a marker of platelet activation) in 9 patients with type 2B vWD before, and in 4 patients also following the infusion of 1-desamino-8-d-arginine vasopressin (DDAVP). Three patients presented a persistent decrease of platelet counts in the resting condition. GC levels were within the normal range, regardless of the platelet counts, in all but one patient who presented, on the other hand, a normal platelet count. Moreover, platelets expressed normal amounts of P-selectin on their surface, regardless of platelet counts. These findings suggest that the thrombocytopenia observed in type 2B vWD is not due to platelet activation and subsequent consumption in circulation.Despite a significant, albeit transient, decrease in platelet count, DDAVP did not induce an increase in plasma GC levels, nor enhance P-selectin expression. These observations indicate that the acute post-DDAVP thrombocytopenia in type 2B vWD is not related to platelet activation and consumption. We advance that the post-DDAVP 2B vWF is hemostatically more active, and able to induce agglutination but not aggregation of circulating platelets. This would explain both the prompt recovery of basal platelet counts after the post-DDAVP decrease, and the lack of reported thrombotic complications in this disorder.Therefore, even though 2B vWF is characterized by an enhanced affinity for the platelet surface, its binding to platelet GPIb-IX in the soluble phase is not able to induce true platelet aggregation; vWF thus appears to be mainly an adhesive protein, rather than an aggregating agent.